Estimation of wind sea and swell using shipboard measurements – A refined parametric modelling approach. (January 2016) - Montazeri, Najmeh; Nielsen, Ulrik Dam; Juncher Jensen, Jørgen
Abstract : Highlights: A method for estimation of wind sea and swell using ship responses is proposed. The estimation method is based on JONSWAP model for double-peaked spectra. The estimated main integral parameters of waves are fairly close to the true values. Abstract: Shipboard wave estimation has been of interest in recent years for the purpose of decision support. In this paper, estimation of sea state is studied using ship responses and a parametric description of directional wave spectra. A set of parameters, characterising a given wave spectrum is estimated through an optimisation problem using global search basin with proper constraints. The cost function is established based on the difference between the energies of a set of measured ship responses and the corresponding theoretical spectral moments. A partitioning procedure is applied, which is able to separate swell components from wind seas.